Myoclonus in Ataxia–Telangiectasia. (13th March 2015) - Termsarasab, Pichet; Yang, Amy C.; Frucht, Steven J.
Background: Various movement disorders can be found in ataxia–telangiectasia (AT), including ataxia, dystonia, chorea, and myoclonus, but myoclonus has rarely been described as the predominant feature in AT. Case Report: We report two AT patients with prominent myoclonus, illustrating an unusual presentation of this disorder. Sequencing of the ATM gene in the first patient revealed a homozygous truncating mutation, c.5908C>T (p.Q1970*) in exon 38 of the ATM gene, which has been previously reported as a founder mutation in the Costa Rican population. Discussion: Myoclonus can be a predominant or presenting feature in AT, even without dystonia.